THU0540 Autologous Osteoblastic Cells versus Concentrated Bone Marrow Implantation in Osteonecrosis of The Femoral Head: A Randomized Controlled Single Blind Study. (15th July 2016) - Gangji, V.; Toungouz, M.; Lechanteur, C.; Beguin, Y.; Baudoux, E.; De maertelaer, V.; Pather, S.; Katz, R.; Ino, J.; Egrise, D.; Malaise, M.; Hauzeur, J.-P.
Abstract : Background: Non traumatic osteonecrosis (ON) of the femoral head is characterized by epiphyseal necrosis leading to femoral head collapse and hip replacement. ON can be seen as a vascular, mesenchymal and bone cells disease. Indeed, it was shown that implantation of bone marrow concentrate (BMC) containing mesenchymal stem cells (MSC) could delay ON progression and improve symptoms. Then, the possibility was raised that a cell-based medicinal product consisting in a population of autologous osteoblastic cells (OB) could be more efficacious than BMC in early stages ON of the femoral head. Objectives: This study was undertaken to evaluate the efficacy of OB cells implantation in a randomized comparison with BMC implantation in early stages (prefractural ARCO stage 1 or 2) ON of the femoral head. Methods: Patients with stage 1 or 2 ON were included in a randomized controlled single blind trial. Hips were randomized to receive a core decompression procedure followed by BMC or OB cells implantation. In the BMC group, 410.6±84.9 ml of BM was harvested from the iliac crest and concentrated to 41.8±10.9 ml. In the OB group, MSC were isolated from BM aspirate (48.8±17.7 ml), expanded and differentiated ex vivo under autologous conditions to obtain a population of OB cells (18.6±4.3x10 6 cells). Hip pain, WOMAC score and X-Rays were assessed at 3, 6, 12, 24 and 36 months. The primary endpoint was the proportion of responders at 24 months. A responder was defined as the absence of progression to a fractural stage (stage 3 or 4) and a clinically significant pain improvement. Results: From 72 hips randomized, 60 hips (30 hips per group) were analyzed as the ITT efficacy cohort (50.6±11.8 years). Baseline demographic data, risk factors, location and size of ON and symptoms were not statistically different between groups. At 24 months, 70% versus 40% of hips ( p <0.05) and at 36 months, 60% versus 33% of hips ( p <0.05) in OB and BMC groups respectively were considered as responders. The rate of progression to stage 3 or 4 was in favor of the OB group. At 24 months, 20% versus 40% of hips (NS) and at 36 months, 20% versus 47% of hips ( p <0.05) in OB and BMC groups respectively progressed to stage 3 or 4. A decrease in hip pain was observed in the OB group compared to the BMC group at 24 months (NS) and 36 months ( p <0.05). Finally, patients treated with OB cells demonstrated a decrease in joint symptoms at 24 and 36 months according to the WOMAC score. Overall, 117 SAE (47 in the BMC group and 70 in the OB group) were reported of which 4% (5 SAE) were possibly related to the procedure or the cell therapy products. Conclusions: This study showed that OB cells implantation in ON lesion could be more efficacious than BMC treatment to delay the evolution to subchondral fracture and to reduce pain in ON of the femoral head. Disclosure of Interest: V. Gangji Consultant for: Bone Therapeutics, M. Toungouz: None declared, C. Lechanteur: None declared, Y. Beguin: None declared, E. Baudoux: None declared, V. De maertelaer: None declared, S. Pather: None declared, R. Katz: None declared, J. Ino Employee of: Bone Therapeutics, D. Egrise: None declared, M. Malaise: None declared, J.-P. Hauzeur Consultant for: Bone Therapeutics